Intermittent state estimation for nonlinear delay systems with redundant communication channels. (9th March 2022) - Guo, Yuru; Yang, Lixin; Rao, Hongxia; Lin, Ming; Xu, Yong
Abstract: This article investigates state estimation for discrete‐time nonlinear systems with Markov delay, where a redundant communication channel is considered to improve transmission reliability. As the channel capacity is limited, we use two Bernoulli stochastic variables to describe the packet dropout conditions of the main channel and the redundant one. In addition, a mode‐dependent estimator based on both the current state and the delayed state is designed. Combining with an intermittent approach, the efficiency of the estimator is improved. An augmented estimation error system is proposed to deal with the Markov delay in the nonlinear system. Subsequently, a sufficient condition is obtained to ensure the asymptotic stability of the augmented error system by constructing a Lyapunov function, and the gains of the intermittent estimator are derived. Finally, a numerical example of a moving vehicle is utilized to illustrate the developed results.